Relationships Among Live Body Weight and Some Body Measurements in Sudanese Kenana Bulls - Musa, AM; Idam, NZ; Elamin, KM (ANIMAL PRODUCTION, 2012)
Abstract. The phenotypic relationship between live body weight (kg) and body measurements (cm) for Sudanese bulls is explored. In this research, data from one visit survey were used to estimate the relationships between live body weight and some body measurements of Sudanese Kenana bulls. General linear model analysis with multivariate ANOVA when all physical variables were response and animal live body weight groups (kg) as independent, and simple linear Pearsons correlation were formed between live body weight (Bwt), Heart girth (HG), Heart girth at hump (HTH), Body length (Bl) and Abdominal girth (ABG). The results revealed the best linear correlation between body weight and measurements was heart girth at hump (0.65, 0.66 and 0.73) respectively, for live body weight groups. The obtained linear correlation coefficients were relatively highly accurate indicators of live body weight. This suggests that live body weight could be estimated accurately by body measurements in Sudanese Kenana Bulls. Keywords: live body weight, body measurements, correlation, Kenana bulls, Sudan Abstrak. Dikaji hubungan fenotipik antara bobot badan hidup (kg) dengan beberapa ukuran tubuh (cm) pada sapi Sudan. Data diperoleh dari survei untuk menduga hubungan antara bobot badan hidup dengan beberapa ukuran tubuh sapi Kenana Sudan jantan. General Linier Model (GLM) dengan anova multivariat diterapkan pada semua peubah fisik sebagai respon dan kelompok bobot badan hidup ternak (kg) sebagai peubah bebas. Analisis korelasi linier Pearson digunakan untuk bobot hidup tubuh (BWT), lingkar dada (HG), lingkar dada pada punuk (HTH), panjang tubuh (Bl) dan lingkar perut (ABG). Hasil penelitian menunjukkan hubungan linear terbaik antara bobot badan dengan lingkar dada pada punuk masing-masing 0,65, 0,66 dan 0,73 berturut-turut pada kelompok bobot badan.  Koefisien korelasi linear yang diperoleh menunjukkan indikator yang relatif akurat dari bobot badan hidup. Hal ini menunjukkan bahwa bobot badan hidup dapat diduga secara akurat dengan ukuran tubuh pada sapi jantan Kenana Sudan.Kata kunci: bobot hidup badan, ukuran tubuh, korelasi, sapi Kenana, Sudan AM Musa et al/Animal Production 14(3):187-191, September 2012